Hydatidiform Mole—Between Chromosomal Abnormality, Uniparental Disomy and Monogenic Variants: A Narrative Review - Andreea Florea; Lavinia Caba; Ana-Maria Grigore; Lucian-Mihai Antoci; Mihaela Grigore; Mihaela I. Gramescu; Eusebiu Vlad Gorduza (Life, 2023)
A hydatidiform mole (HM) or molar pregnancy is the most common benign form of gestational trophoblastic disease characterized by a proliferation of the trophoblastic epithelium and villous edema. Hydatidiform moles are classified into two forms: complete and partial hydatidiform moles. These two types of HM present morphologic, histopathologic and cytogenetic differences. Usually, hydatidiform moles are a unique event, but some women present a recurrent form of complete hydatidiform moles that can be sporadic or familial. The appearance of hydatidiform moles is correlated with some genetic events (like uniparental disomy, triploidy or diandry) specific to meiosis and is the first step of embryo development. The familial forms are determined by variants in some genes, with NLRP7 and KHDC3L being the most important ones. The identification of different types of hydatidiform moles and their subsequent mechanisms is important to calculate the recurrence risk and estimate the method of progression to a malign form. This review synthesizes the heterogeneous mechanisms and their implications in genetic counseling.